PENERAPAN SENAM TERHADAP KUALITAS TIDUR IBU HAMIL TRIMESTER III DI PUSKESMAS TANJUNG BALAI KARIMUN - Nilma; Yenni Aryaneta; T.Marzila Fachnawal; Miftahul Jannah (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
According to the World Health Organization (WHO), the global prevalence of insomnia, which is a sleep disorder in pregnant women worldwide, is 41.8%. Pregnant women who have difficulty getting enough sleep can make the condition of pregnant women decrease, their concentration decreases, their bodies feel sore, they tire easily, they are not enthusiastic about working and they tend to be more emotional. Pregnancy exercise is one of the activities in health services during pregnancy. The aim of the study was to provide midwifery care to pregnant women for Mrs. E at 32 weeks of gestation with sleep pattern disturbance problems in her third trimester of pregnancy, by doing pregnancy exercises. This report method is a case study, data collection techniques with interviews, observation and documentation. Pregnancy exercise is carried out at least twice a week for 30 minutes. Pregnancy exercise will have a relaxing effect on pregnant women which can affect the improvement of sleep quality for pregnant women, thus causing pregnant women to have good sleep quality. For mothers, it is expected that physical exercise during pregnancy will provide many benefits, especially if pregnancy exercise is carried out regularly and on a scheduled basis, the effects of the pregnancy exercise will be felt on health, especially during pregnancy.